1931 Ark. Acts 705-06, § 3 - (:unkn) unknown (My University, 1931)
Act of Mar. 26, 1931, No. 225, § 3: Prohibited selling, giving away, or to have interest in the sale or giving away of any firearm type commonly known as a machine gun.
Keywords: TRANSFER - MACHINE GUNS